2016
DOI: 10.29052/2413-4252.v2.i1.2016.1-6
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Social and Cultural Barriers Present for Women Seeking Healthcare in Rural Communities of Karachi, Pakistan

Abstract: Study was an interview-based cross-sectional survey with an objective of investigating if there are any social or cultural factors present in rural areas, which makes it difficult for women living in these communities to seek proper health care services. The subjects of this study were rural women who came to receive treatment for their gestation and related complications at Koohi Goth Hospital in Karachi, Pakistan. The variables that were explored included the level of education, socioeconomic status, social/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In addition, many barriers to the uptake of referrals identified in this study were system-related and could not be addressed by the LHW referral programme alone. Similar to other rural contexts in South Asia [ 29 , 30 ], we identified user fees and long distances to the facilities as major factors affecting patients’ decision-making. Also, in this specific context, the perceived poor quality and dissatisfaction with services in government hospitals were a major barrier.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, many barriers to the uptake of referrals identified in this study were system-related and could not be addressed by the LHW referral programme alone. Similar to other rural contexts in South Asia [ 29 , 30 ], we identified user fees and long distances to the facilities as major factors affecting patients’ decision-making. Also, in this specific context, the perceived poor quality and dissatisfaction with services in government hospitals were a major barrier.…”
Section: Discussionmentioning
confidence: 91%
“…Gender inequities are deeply entrenched in Pakistan. The underlying gender structures which offer men numerous material benefits and decision-making authority contribute to women’s relatively lower uptake of health services [ 30 , 33 ]. Previous studies in the country have shown that even those who have some source of income to facilitate travel to the hospital often choose not to – reflecting the values and ideals of being a good wife and putting the family first [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%